Membelajarkan Anak Autis Menggunakan Media Visual Kinestetik - Sri Hariyani; Rahaju Rahaju (Aksiologiya: Jurnal Pengabdian Kepada Masyarakat, 2019)
The community capacity building program in reducing disaster risk aims to realize the Bandung Rejo village as a disaster resilient village. Efforts made to achieve community capacity building include: (1) institutional aspects through the establishment of Disaster Risk Management forums (DRR) and Community Disaster Preparedness Teams (CDPT), (2) aspects of capacity building through dissemination and training in the preparation of disaster management plans and contingency plans , (3) aspects of the implementation of disaster management through a program to create a threat map and create disaster warning signs. The establishment of DRR and CDPT forums has a strategic role in minimizing disaster risk. The results achieved from the socialization and training were the availability of Bandung Rejo village disaster risk analysis document. The document can be a reference in making development policies in the village. Based on the results of the analysis conducted by the forum that Bandung Rejo village had a flood hazard level in the medium category. The results of identification and analysis obtained two flood-prone points that were able to reach agricultural land and facilities and infrastructure facilities. The implementation of community capacity building programs in Bandung Rejo village can provide stimulus to local governments and the public about the importance of disaster anticipation.